Numerical investigation on reinforcement requirement for piles embedded in clay - Salman, F.A.; Fattah, M.Y.; Mohammed, M.M.; Hashim, Roslan (2010)
In this study the necessity of reinforcement in concrete pile (bored or driven) is assessed. The soil was assumed to be unsaturated and homogeneous clayey soil. Throughout the study, a finite element computer program was developed and the pile was modeled as a beam-on-elastic foundation. The soil is represented by discrete spring. The stiffness of each spring is considered to be linearly variable with depth. The moment loading, lateral loading, pile length, pile diameter, in addition to the angle of internal friction; soil density and soil cohesion were taken as parameter to study their effect on the extent of reinforcement along the pile shaft. It is concluded that for piles embedded in clay, a length of reinforcement not less than one-half the pile length is needed.